Early insight on how climate action can benefit health in rural India - Vijay S Limaye; Sameeha Hossain; Ritika Kapoor; Dhilsha Jubair; Charu Lata (The Journal of Climate Change and Health, 2025)
Introduction: India faces severe health impacts from climate change. While urban-focused initiatives like the National Clean Air Programme and heat action plans aim to address dangerous exposures, rural regions, home to over 60% of India's population, remain underprioritized in mitigation and adaptation measures. To address this gap, the Self Employed Women's Association (SEWA) and Natural Resources Defense Council (NRDC) implemented the Hariyali Gram (Green Village) initiative, deploying climate-friendly technologies to support improved lighting, cooling, irrigation, and clean cooking in pilot villages beginning in 2019. Methods: In March 2024, 90 household surveys were conducted in Nagano Math, a village of 256 households in the state of Gujarat, assessing air quality effects, indoor thermal comfort, and health impacts following the implementation of climate-friendly renewable energy solutions. Results: Survey responses (n-86) indicated substantial awareness of indoor air pollution from traditional cooking methods, with 88% of respondents acknowledging its impact. Nine households received biogas installations and 78% noted improved indoor air quality, while 66 % observed enhanced outdoor air quality and 56% respondents reported health benefits from adopting cleaner cooking for themselves or other members of the household. Of 19 households that installed cool roofs as part of the program, 37% reported improved thermal comfort indoors. Discussion: Climate actions in this village are delivering health and environmental gains to this community with benefits are reported in about half of households. Findings of our preliminary survey in a single village suggest scaling up climate interventions across rural India could deliver substantial improvements in living conditions.